Behavioral factors influencing individual investors’ decision making in Vietnam market - Quang, Luu Thu; Linh, Nguyen Duy; Nguyen, Diep Van; Khoa, Duong Dang (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Using behavioral factors (mood, overconfidence, underreaction, overreaction, and herding behavior) as proxy variables in the Vietnamese stock market, this article tries to explore the link between investor demographics (gender, age, experience, and educational ability) and their investment decisions. This study compiles information from a structured questionnaire survey of 400 local, international, institutional, and individual investors in Vietnam. It employed partial multiple regression to examine how investors’ demographic variables affected their investment choices using behavioral traits as mediator variables. According to the results, investor emotion, overconfidence, over/underreaction, and herd behavior all have a large impact on investing decisions. Additionally, investors’ investing selections are significantly and favorably influenced by their age, gender, and degree of education. Although experience does not have a significant effect on financial decisions, investors start to ignore emotional aspects as they become more experienced.